Pro-environmental employee engagement: the influence of pro-environmental psychological capital, pro-environmental job resources, and perceived corporate environmental responsibility - Albrecht, Simon L.; Donnelly, Teagan; Frenkiel, Michael; Rajic, Stefan K.; Kavadas, Vicki; Leiter, Michael P. (Frontiers in Sustainability, 2023)
For organizations to achieve their environmental obligations and objectives, they need employees to actively engage with environmental policies, practices, procedures, and initiatives. Based on engagement theory, a model is proposed that shows how perceived corporate environmental responsibility, pro-environmental job resources, and pro-environmental psychological capital influence employee pro-environmental engagement at work. Survey responses were collected from a Prolific sample of 347 full-time and part-time employees, aged 18–80, working within Australian organizations across a range of occupations. Confirmatory factor analysis and structural equations modeling provided broad support for the measures and the relationships proposed in the model. The model explained 64% of the variance in pro-environmental job resources, 90% of the variance in pro-environmental psychological capital, and 92% of the variance in pro-environmental engagement. Overall, the results suggest that for employees to feel enthusiastic and involved in pro-environmental initiatives at work, an integrated approach that takes account of perceived corporate environmental responsibility, pro-environmental job resources, and pro-environmental psychological capital is required. The results also provide brief, defensible measures of pro-environmental PsyCap, pro-environmental job resources and pro-environmental engagement that can be used to assess and target employee attitudes toward pro-environmental initiatives and opportunities. As such, the pro-environmental engagement model can help guide the design and implementation of evidence-based employee-focused interventions that will help achieve environmental sustainability objectives.